Effect of processing techniques on the 3D microstructure of poly (l‐lactic acid) scaffolds reinforced with wool keratin from different sources. Issue 48 (10th September 2015) - Puglia, Debora; Ceccolini, Romina; Fortunati, Elena; Armentano, Ilaria; Morena, Francesco; Martino, Sabata; Aluigi, Annalisa; Torre, Luigi; Kenny, Jose M; Pantani, Prof. Roberto; Turng, Prof. Lih‐Sheng
ABSTRACT The aim of this work was the analysis of morphologies of poly (l‐lactic acid)/keratin tridimensional scaffolds developed by using two main solvent based techniques: solvent casting particulate leaching in the presence of paraffin microspheres as porogen, and thermally induced phase‐separation process. Keratins from different sources were used. Specifically, keratin from Merino wool (KM) and Brown Alpaca (KA) were dispersed in dioxane or 1, 4‐dioxane/water mixture and then the keratin structure after interaction with 1.4‐dioxane was investigated by means of electrophoresis and spectroscopic analysis. A detailed morphological characterization of the scaffold systems obtained by the two different methods was performed by using field emission scanning electron microscopy. The effect of porogen content, solvent composition and processing parameters, such as the influence of keratin presence (1 wt %) and source (KA and KM) were evaluated. The results reveal that 1, 4‐dioxane, used as based solvent in the two selected processes, does not negatively affect the keratin structure. A slight change in the procedure parameters, such as porogen content or solvent/non‐solvent ratio, significantly affects the resulting porosity and architecture of the obtained PLLA and PLLA/keratin scaffolds. Both keratins can be considered as suitable fillers able to modify the pore architecture and interconnection of three‐dimensional PLLA/keratin porous composites obtained by the two different solvent assisted techniques. Of note, both composites are biocompatible, as demonstrated by the culture adult bone‐marrow mesenchymal stem cells without signs of toxicity. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42890.